Internal electrochromism in vanadium pentoxide xerogel films. (15th March 2016) - Yakovleva, D.; Pergament, A.; Berezina, O.; Boriskov, P.; Kirienko, D.; Pikulev, V.
Abstract: We describe the internal electrochromic effect in V2 O5 xerogel films caused by the redistribution of hydrogen ions inside the film, instead of insertion from the outside, i.e. from an electrolyte, as in the case of conventional electrochromism. A hypothesis is put forward according to which the mechanism of this electrochromic effect is associated with formation of red-colored hexa- and (or) deca-vanadic acid inclusions inside the vanadium pentoxide layers. This model is supported by the calculated data of energy characteristics of V–O chemical bonds in V2 O5 octahedra layers of xerogel, as well as by the experimental results of XRD, FTIR, and optical spectroscopy.